PMO AS A SERVICE: UMA ANÁLISE DA COMPETÊNCIA PELA LENTE FRANCÓFONA - Fernandes, Bruno Dornelas de Azevedo (2021)
This study uses the French notion of competence to investigate the competence mobilized by the PMO AAS while working. This is a qualitative approach with the strategy of exploring a new or little-studied phenomenon. As a method of data collection, it uses semi-structured interviews and as a method of data analysis, coding is used according to grounded theory. The study approaches the professional acting as PMO AAS as the research subject. The results show some competences mobilized by the PMO AAS for specific functions faced during real work situations, in addition to considering the role of the context that may or may not influence their performance. An example: in a situation of organizational restructuring that negatively impacted the project schedule, negotiation, conflict management and communication skills were mobilized by the professional PMO AAS to be competent in the task of monitoring and controlling the project's performance. This research systematizes and presents the French aspect of competence to study the phenomenon of PMO AAS, expanding the understanding of what is a recent and little studied phenomenon. And it ends up contributing empirically to the literature on PMO insofar as the findings indicate possibilities to format a trail of training better directed to the real situations of the project office, where organizations can take advantage to train their collaborators as well as the workers can enhance their employability.